Effect of protein level and stocking density on growth performance, feed utilization and resistance of Nile tilapia (Oreochromis niloticus) to infection against aeromonas septicemia (Aeromonas hydrophila) - Omar E.; Al Sagheer F.M.; Nour A.M.; Abou-Akkada A.R. (Feeding tomorrow's fish, 1997)
A fourteen week laboratory feeding trial was conducted to ascertain the effect of two dietary crude protein levels (30 and 40 CP per cent) and stocking densities (10, 30 and 40 fish/105 litre aquarium) on growth performance, feed and nutrient utilisation, and the resistance of Nile tilapia (Oreochromis niloticus) to infection with Aeromonas hydrophila. Fish were reared within indoor glass aquaria (100 by 30 by 40 cm) containing dechlorinated water supplemented with aeration and temperature controlled at 28 degrees C plus minus 1 for the duration of the experiment. The results showed that growth performance of tilapia fingerlings was significantly (P less than 0.05) reduced at the higher dietary protein level and stocking densities. Feed and nutrient efficiency was also significantly (P less than 0.05) reduced at the higher dietary protein and stocking densities tested. Moreover, at the end of the 14-week experiment, the immune response of tilapia after immunisation within formalin killed A. hydrophilla bacteria (FKB) was studied; the results of antibody titer of the immunised fish after 28 days differing significantly (P less than 0.05) between individual treatments. The highest titer was obtained with fish stocked at the lowest stocking density (10 fish per aquarium) and fed the lowest protein diet (30 per cent CP). By contrast, the lowest antibody titer was found in fish reared at the highest stocking density (40 fish per aquarium) and fed the lowest level of dietary protein (30 per cent CP). Percentage survival rate after bacterial challenge was also highest for fish reared at the lowest stocking density (10 fish/aquarium) and fed the lowest dietary protein level (30 per cent CP). The results clearly showed that fish growth was best at the lowest stocking density and low dietary protein level tested, and that these parameters significantly affected the capability of fish to resist infection against Aeromonas septicemia.
Workshop of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1996/06/24-26, Mazarrón (Spain)